Effect of age of shell vial monolayers on detection of cytomegalovirus from urine specimens. - Fedorko, D P (1989)
The effect of age of MRC-5 cell monolayers in shell vials on the detection of cytomegalovirus (CMV) from urine was evaluated. When the AD169 strain of CMV was used, 8-day-old monolayers had a higher mean count of fluorescent foci than 15-day-old monolayers did (5.78 versus 2.86) (P less than 0.02) and were more frequently positive (21 of 23 shell vials versus 14 of 22 shell vials) (P less than 0.04). Commercial shell vials used for clinical specimens were evaluated in groups of 8- to 11-, 12- to 15-, and 8- to 15-day-old monolayers. When compared with laboratory-prepared shell vials ranging in age from 3 to 9 days, commercial shell vials had a lower number of fluorescent foci in all groups (P less than 0.03, P less than 0.0001, and P less than 0.0001, respectively), the 12- to 15- and 8- to 15-day-old groups were less frequently positive (P less than or equal to 0.02 and P less than 0.02, respectively), and all three groups were more susceptible to the toxic effects of urine (P less than 0.0001, P less than 0.01, and P less than 0.0001, respectively). For all 191 specimens cultured (8- to 15-day-old group), one or both monolayers were destroyed in 60 (31.4%) specimens compared with 9 (4.7%) specimens toxic to laboratory-prepared shell vials (P less than 0.0001). Both the decreased sensitivity of older MRC-5 cells and the increased sensitivity to the toxic effects of urine made commercial shell vial less sensitive than laboratory-prepared shell vials for the detection of CMV.